DEEPER UNDERSTANDING OF MODERN LEARNING: HOW TECHNOLOGY OPENS THE STUDENTS' INTERESTS - Susilo Gondo (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2024)
Technology plays a crucial role to stimulate students' interest in this modern era. This article aims to explore the impact of the latest technology on the learning process and how these innovations can open students' interests. Through an analytical approach, the researcher has investigated various technological tools and platforms that facilitate interactive learning and personalization of curriculum. Besides, this article examined the challenges might arise with the integration of technology in modern learning contexts. The research is library research, with documentary data collection methods, and analysis using content analysis. The results of this study aimed to provide an in-depth understanding of how technology can be a catalyst to strengthen students' interests, open up new opportunities, and increase the effectiveness of the learning process in this digital era.